2012
DOI: 10.3389/fmicb.2012.00416
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reduction of Chromate in the Presence of Nitrate by Three Nitrate Respiring Organisms

Abstract: A major challenge for the bioremediation of toxic metals is the co-occurrence of nitrate, as it can inhibit metal transformation. Geobacter metallireducens, Desulfovibrio desulfuricans, and Sulfurospirillum barnesii are three soil bacteria that can reduce chromate [Cr(VI)] and nitrate, and may be beneficial for developing bioremediation strategies. All three organisms respire through dissimilatory nitrate reduction to ammonia (DNRA), employing different nitrate reductases but similar nitrite reductase (Nrf). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 62 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…Like nitrate, perchlorate can serve as an electron acceptor in biology. 19 For example, an elevated nitrate level has been associated with chromium, 20,21 and uranium. 22,23 Thus successful strategies for the bioremediation of heavy metal contaminated sites must address the influence of nitrate in the process.…”
Section: Nitrate Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like nitrate, perchlorate can serve as an electron acceptor in biology. 19 For example, an elevated nitrate level has been associated with chromium, 20,21 and uranium. 22,23 Thus successful strategies for the bioremediation of heavy metal contaminated sites must address the influence of nitrate in the process.…”
Section: Nitrate Reductionmentioning
confidence: 99%
“…22,23 Thus successful strategies for the bioremediation of heavy metal contaminated sites must address the influence of nitrate in the process. 21 …”
Section: Nitrate Reductionmentioning
confidence: 99%
“…Interestingly, Geobacter species have been reported previously to reduce toxic hexavalent chromium [Cr(VI)] to trivalent chromium [Cr(III)] (Chovanec et al 2012;Tuo et al 2013), thus this community member may have an ability to resist this toxin. Within the dominant phyla Bacteroidetes and Proteobacteria, several OTUs correlated positively with Zn, which has been documented previously in another study (Azarbad et al 2015).…”
Section: Impact Of Available Metal On Microbial Otusmentioning
confidence: 99%
“…The host bacteria with a broad adaptability to the environment can be selected for future studies. In biodegradation, the main problems to be solved are the effects of other pollutants on reducing Cr (VI), in which the most common is the interference of metal ions (20). In the present study, it was shown that the majority of common metal ions did not inhibit the Cr (VI) reduction in engineered bacteria, whereas Cu 2+ , Co 2+ and Pb…”
Section: Discussionmentioning
confidence: 71%
“…The Cr (VI) concentration in the medium at different culture temperatures (20,25, 30, 37, 40 and 50˚C) was also detected. As shown in Fig.…”
Section: Effects On Cr (Vi) Elimination Capability By the Culturing Cmentioning
confidence: 99%